2018
DOI: 10.1002/ange.201807435
|View full text |Cite
|
Sign up to set email alerts
|

Spontaner metallfreier Wasserstofftransfer zwischen Amminboranen und Iminoboranen

Abstract: Wirb erichtenh ier über den ersten spontanen und metallfreien Wasserstofftransfer zwischen Amminboran (NH 3 BH 3 )u nd Iminoboranen bei Raumtemperatur.D FT-Rechnungen belegen einen konzertierten H + /H À -Transfer von NH 3 BH 3 mit einer Aktivierungsenergie weit unter der vergleichbarer Wasserstoffübertragungsreaktionen. Zudem konnten durch Umsetzung von Iminoboranen mit Amminboranen neue B,N-disubstituierte Aminoborane isoliert werden, von denen bisher nur wenige Vertreter bekannt sind. Dieser erfolgreicheW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Recently, Braunschweig and co‐workers reported the first iminoborane that can rapidly dehydrogenate ammonia–borane at room temperature . They showed that 1 equivalent of tert ‐butyl substituted iminoborane 5 (Scheme ) rapidly reacts with 1 equivalent of AB, forming the expected aminoborane 6 , along with borazine and other dehydrogenated products.…”
Section: Stoichiometric Dehydrogenationmentioning
confidence: 92%
“…Recently, Braunschweig and co‐workers reported the first iminoborane that can rapidly dehydrogenate ammonia–borane at room temperature . They showed that 1 equivalent of tert ‐butyl substituted iminoborane 5 (Scheme ) rapidly reacts with 1 equivalent of AB, forming the expected aminoborane 6 , along with borazine and other dehydrogenated products.…”
Section: Stoichiometric Dehydrogenationmentioning
confidence: 92%